2020
DOI: 10.1186/s40359-020-00424-2
|View full text |Cite
|
Sign up to set email alerts
|

Adult attachment style and maternal-infant bonding: the indirect path of parenting stress

Abstract: Background: The quality of maternal-infant bonding is related to important child outcomes. The literature has assumed that the ability to form relationships is a relatively stable trait, and research studies have suggested that a mother's attachment style in close adult relationships is related to mother-infant bonding. The transition to parenthood is also often stressful, and the adult attachment style may relate to parenting stress in the first year after birth. Such stress could possibly have a negative rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 41 publications
(54 reference statements)
4
30
0
1
Order By: Relevance
“…For instance, Bieleninik et al [46] observed that paternal stress mediates the relationship between paternal anxiety and paternal postpartum bonding. Our results are partially in agreement with those obtained by Nordahl et al [69] who found no direct relationship between adult attachment style dimensions and bonding with the child when parental stress was included as a mediator. However, when examining each adult attachment domain with Maternal-Infant bonding, Nordahl et al [69] found that the relationship between those two variables was mediated by parenting stress.…”
Section: Is Postpartum Bonding Associated With Maternal Mental Health (Depression Symptoms Anxiety and Stress)?supporting
confidence: 93%
See 1 more Smart Citation
“…For instance, Bieleninik et al [46] observed that paternal stress mediates the relationship between paternal anxiety and paternal postpartum bonding. Our results are partially in agreement with those obtained by Nordahl et al [69] who found no direct relationship between adult attachment style dimensions and bonding with the child when parental stress was included as a mediator. However, when examining each adult attachment domain with Maternal-Infant bonding, Nordahl et al [69] found that the relationship between those two variables was mediated by parenting stress.…”
Section: Is Postpartum Bonding Associated With Maternal Mental Health (Depression Symptoms Anxiety and Stress)?supporting
confidence: 93%
“…Our results are partially in agreement with those obtained by Nordahl et al [69] who found no direct relationship between adult attachment style dimensions and bonding with the child when parental stress was included as a mediator. However, when examining each adult attachment domain with Maternal-Infant bonding, Nordahl et al [69] found that the relationship between those two variables was mediated by parenting stress. This demonstrated that parenting stress is important to the quality of maternal bonding with a child.…”
Section: Is Postpartum Bonding Associated With Maternal Mental Health (Depression Symptoms Anxiety and Stress)?supporting
confidence: 93%
“…However, various studies investigating the specific associations of avoidant and anxious attachment orientations and mother–infant bonding report inconsistent findings, similarly to our findings. For example, only avoidance was a significant predictor of mother–infant bonding when controlling for demographic variables and maternal mental health history ( 29 ). In another study, there was no direct relationship between attachment and mother–infant bonding; however, anxious attachment was associated with postpartum depression, and depressive symptoms predicted impaired bonding ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies examined the association between those concepts with inconclusive results pattern. On the one hand, during the transition to motherhood, insecure attachment (anxious and avoidant) was associated directly with bonding difficulties among parents ( 27 ) and indirectly mediated by postpartum depression among mothers ( 28 ) or mediated by parenting stress ( 29 ). On the other hand, Van Bussel et al ( 9 ) reported a weak correlation between mother–infant bonding and attachment style while maternal romantic attachment style predicted attachment with the fetus in the antenatal, but not with the baby in the postpartum period ( 30 ) and only women with a dual/disorganized attachment style reported lower bonding than with women with secure and insecure attachment styles ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…The avoidance subscale assesses discomfort with dependence and intimate self-disclosure towards the partner. Recently, other authors describe the constructs as different constructs as well [ 4 , 52 ]. We cannot completely rule out that there is the slight possibility that the way the mother responded to one questionnaire affected the way she responded to the second one.…”
Section: Discussionmentioning
confidence: 99%